The Natural History of Uterine Leiomyomas: Morphometric Concordance with Concepts of Interstitial Ischemia and Inanosis - Gordon P. Flake; Alicia B. Moore; Norris Flagler; Benita Wicker; Natasha Clayton; Grace E. Kissling; Stanley J. Robboy; Darlene Dixon (Obstetrics and Gynecology International)
Based upon our morphologic observations, we hypothesize and also provide morphometric evidence for the occurrence of progressive developmental changes in many uterine fibroids, which can be arbitrarily divided into 4 phases. These developmental phases are related to the ongoing production of extracellular collagenous matrix, which eventually exceeds the degree of angiogenesis, resulting in the progressive separation of myocytes from their blood supply and a condition of interstitial ischemia. The consequence of this process of slow ischemia with nutritional and oxygen deprivation is a progressive myocyte atrophy (or inanition), culminating in cell death, a process that we refer to as inanosis. The studies presented here provide quantitative and semiquantitative evidence to support the concept of the declining proliferative activity as the collagenous matrix increases and the microvascular density decreases.